The Effect Of Grasp Technique Toward Students’ Reading Comprehension at Fourth Semester Of STKIP YPM Bangko Academic Year 2014/2015 - Oktawati, Herysa (STKIP YPM Bangko, 2017)
This research was an experimental research. It was conducted at STKIP YPM Bangko. The design of this research was quasi experimental research. Population of this research was Fourth year students with the total population was 92. The sample was taken by cluster sampling. To collect the data the researcher used reading comprehension tests. The data were analyzed by SPSS 16.0 of t-test. The result finding shows that GRASP technique gave significant effect on students’ reading comprehension than conventional technique. Based on the result finding, it can be concluded that GRASP Technique is effective to improve students’ reading comprehension. This technique could be used in teaching reading comprehension at students English Department of STKIP YPM Bangko.